Effect of Poling on Photocatalysis, Piezocatalysis, and Photo–Piezo Catalysis Performance of BaBi4Ti4O15 Ceramics. Issue 2 (15th November 2022) - Kumar, Pushpendra; Vaish, Rahul; Sung, Tae Hyun; Hwang, Wonseop; Park, Hyeong Kwang Benno; Kumar, Anuruddh; Kebaili, Imen; Boukhris, Imed
Abstract: This study focuses on analyzing the poling effect of BaBi4 Ti4 O15 (BBT) on the basis of photo and piezo‐catalysis performance. BBT powder is prepared via a solid state reaction followed by calcination at 950 °C for 4 h. BBT is characterized by an X‐ray diffractometer, scanning electron microscopy, Raman spectroscopy, and X‐ray photoelectron spectroscopy. The optical bandgap of BBT is evaluated with the help of Tauc's plot and found to be 3.29 eV, which comes in the photon energy range of ultra‐violet radiation. BBT powder is poled by using Corona poling in the presence of 2 kV mm −1 of electric field. An aqueous solution of methyl blue (MB) dye in the presence of UV radiation is used to evaluate the photo/piezocatalysis performance. Photocatalysis, piezocatalysis, and photo–piezo catalysis degradation efficiencies of poled and unpoled BBT powder are tested for 120 min of UV light irradiation. Photo–piezocatalysis shows degradation efficiencies of 62% and 40% for poled and unpoled BBT powder, respectively. Poling of BBT powder shows significant enhancement in degradation performance of MB dye in aqueous solution. Scavenger tests are also performed to identify reactive species. Abstract : BaBi4 Ti4 O15 (BBT) powder is prepared by a solid state reaction with a calcination temperature of 950 °C for 4 h. Half of the BBT powder is poled by corona poling (electric field of 4 kV mm −1 for 4 h). Poled and unpoled BBT powder is tested for photo, piezo, photo–piezo catalysis with methylene blue dye. Results show that poling significantly increases the degradation efficiency.